Prevalencia de úlcera gástrica en cerdos faenados en el camal municipal del cantón Arenillas provincia de El Oro - Vega Conza, Jonathan Mauricio (2014)
In order to determine the rate of prevalence of gastric ulcers in pigs and its relation with the variables: race, age, sex, and origin. We examined 347 stomachs of animals slaughtered in EL CAMAL MUNICIPAL DEL CANTON ARENILLAS PROVINCIA DE EL ORO, since December 2, 2013 until March 5, 2014. The stomachs were opened length wise the greater curve and with top water to extend its inside surface so that it could be seen in its entirety, allowing gross macroscopic examination of the inside surface in order to locate the ulcers; at the time of its location, each ulcer was measured with a ruler to determine the physical dimensions (length x width in centimeters), like physical evidence and located in gastric map previously developed. Four samples were sent to SOLCA for histopathological analysis. The results show a prevalence rate of 6.05% for slaughtered in the slaughterhouse, later was verified great rate prevalence in males (3.45%) were found to females (2.6%) for animals development and fattening up to 8 months (5.79%) for the animals were fed with bananas, fruit peel and human nutrition waste (Lavaza) complement with balanced (6.05%), for mixed races (4.61%) and Pietrain (1.44%); these results are closely related to the origin of the animals of the Parroquías Palmales (4.03%) and La Libertad (0.58%) and the Canton Arenillas (1.44%) place where are the positive animals, therefore the feeding applied. The ulcers were located in the following sequence: 4.89% in the region cardial, 0.87% in the fundic region and 0.29% in the pyloric region of the gastric mucosa. The histopathologic diagnostic showed chronicity of this pathology with activity and commitment specific of the mucosa without apparent damage observed in the rest of the gastric wall (submucosa, muscular and serosa).